Kegiatan Pengabdian Masyakarat Program Mbkm Asistensi Mengajar Di Sungai Selan - Meta Arsita; Vebtasvili Vebtasvili (Insight Power (Kekuatan Wawasan), 2022)
Education is essential for the development of the whole human being to educate and improve the life of the nation's people. The Ministry of Education and Culture offered the Merdeka Learning Campus Merdeka Program (MBKM) in 2020 to prepare tertiary education graduates who are resilient in facing change. The purpose of this community service is to create an educational atmosphere that is meaningful, fun, creative, and dialogic and has a professional commitment to improving the quality of education in Indonesia. This service activity was carried out at 12 Sungai Selan Elementary School, Bangka Belitung Islands Province. The results of this activity get some hard skills and soft skills for students and are useful in the world of work.Keywords: Education, Human Development, Ability, Change, School Activities